مساهمة في تحديد النموذج الرياضي لحركية تحرر البوتاسيوم في ترب حوض العاصي الأوسط - نعناع, أحمد; ترت, محمد; المحمود, فاطمة (Latakia University Journal -Biological Sciences Series, 2018)
أجريت الدراسة المخبرية على بعض ترب السهول البازلتية والفيضية المستثمرة زراعياً بمحاذاة مسيل نهر العاصي ضمن حوضه الأوسط بدءاً من بحيرة الرستن وحتى سد محردة. أما الروافد من المياه المغذية لنهر العاصي والمستخدمة في الزراعة فقد أخذت العينات منها لاستخدامها في دراسة الاستخلاص المتعاقب للبوتاسيوم. وتم كذلك استخدام HNO3 (1 N) لتحرر البوتاسيوم في تجارب منفصلة أخرى. تم إخضاع البوتاسيوم المتحرر إلى النماذج الرياضية والموديلات الحركية ، حيث لوحظ اختلاف في قابلية الترب على تحرر البوتاسيوم وبمعدل يتراوح بين 68.31 – 145.08 ميلي مول / كغ في معاملة حامض النتريك. أظهرت معادلة الانتشار وجود مرحلتين رئيسيتين لعملية تحرر البوتاسيوم. كما لوحظت سرعتان مختلفتان للتحرر. كذلك اختلفت الترب في سعة وسرعة تحرر البوتاسيوم، حيث تراوحت سعة تحرر البوتاسيوم المتبادل بين 1558 – 2784 ملغ / كغ وغير المتبادل بين 218-490 ملغ/ كغ وبسرعة منخفضة, حيث تراوح معدل سرعة تحرر البوتاسيوم بين 173.90 – 323.04 ملغ / كغ / دقيقة. أعلى قيمة تحرر للبوتاسيوم 54.70 ميلي مول /كغ من تربة غور العاصي المعاملة بمياه سد قسطون، وأقل قيمة سجلت 4.18 ميلي مول / كغ من تربة الرستن والمعاملة بمياه سد محردة. أفضل المعادلات الحركية كانت معادلة الانتشار والرتبة الأولى أما معامل سرعة تحرر البوتاسيوم Kd فقد تراوح بين 0.0353 – 0.0390 ميلي مول / كغ / دقيقة بالمعاملة بحامض النتريك, كذلك معامل سرعة التحرر باستخدام المياه تراوحت ما بين 0.0012 – 0.0041 ساعة. Laboratory studies were conducted on some basaltic and flooded soils (6 soils) that were used for agricultural production along the El-Assey River in the middle basin area from Al-Rastan Lake through Maharda dam. Water samples were taken from four different streams feeding into El-Assey River which were used for sequential extraction of soil potassium. A different set of soils were also extracted in 1N HNO3. Values of potassium released from the soils were fitted to mathematical and dynamic models which however showed differences in the ability of soils to release potassium, which ranged from 68.31 to 145.08 mmol K/kg soil in the nitric acid extractant. The diffusion equation showed two different stages and speeds for the rate release of potassium from the soils used in this study. The capacity of soils to release K was also different among soils ranging between (1558-2784 mg K/kg soil) for exchangeable-K and between (218-490 mg K/kg soil) for non-exchangeable-K. The speed release of K was low ranging between (173.90-323.04 mg K/kg soil/min). The highest value for the release of potassium was (54.70 mmol K/kg soil) for El-Assey basin soil extracted with water taken from Qastoon dam, and the lowest value was (4.18 mmol K/kg soil) for Al-Rastan soil and extracted with water sample taken from Maharda dam. The best dynamic equation was first degree diffusion equation which showed a rate for the speed release of K (Kd) between (0.0353-0.0390 mmol K/kg soil/min) nitric acid extraction compared to water extraction (0.0012-0.0041 mmol K/kg soil/h).